The Urban Space ‘Street’ through the Look of the Soundscape. A Methodological Proposal - Quintero, Carolina Alejandra; Recuero López, Manuel (Universidad del Rosario, 2018)
The article presents the methodology of analysis of the street from the soundscape, carried out in the city of Maracaibo - Venezuela. This method is oriented from phenomenology and psychoacoustics. It is make in two phases: The look of the image, and the listener, this is recorded through the technique of the soundwalking, the interpretation of the spectrograms and the surveys. Resulting a multidimensional vision of the street space, which allow to characterize the differences of the landscape from the sound environment, expressing relationships of clarity of the soundscape with the legibility of the urban image of the street.